A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China - Xiang, Lanbin; Xie, Guanglin; Wang, Wenkai (Zootaxa, 2016)
The second species of Pseudotrachystola Breuning, P. yei, sp. nov., is described and illustrated from Hubei, China. The holotype is deposited in the Entomological Museum of Yangtze University. The Chinese name of the new species is designated as 叶氏伪糙天牛.